The influence of Muhammad 'Abduh on Harun Nasution's theological discourse - Ishak, Mohd. Shuhaimi (Hamdard Foundation Press, Pakistan, 2010)
This essay attempts to describe the influence of a prominent Muslim Egyptian scholar in the early nineteenth century, who initiated a reform movement in a scholar from the Indo-Malay world. Muhammad 'Abduh (1265-1323 A.H./1849-1905 C.E.) was regarded as the founder of Islamic modernism, an intellectual trend in religious thought to make Islam capable of facing the advent of modernization. He had advocated the importance of rationalism in the understanding of religion with the hope to liberate the Muslims' mind from stagnation, so as to enable them to progress in tandem with the process of modernization. Hiirun Nasution (1337-1419 A.H./1919-1998 C.E.), a prominent scholar of lndonesia was greatly influenced by 'Abduh's rational approach in religion. The impact of 'Abduh on Harun Nasution was obvious. The latter's work, Muhammad 'Abduh dan Teologi Rational Mu'tazilah was in fact his Ph.D. thesis at the McGill University completed in 1968 under the title The place of reason in 'Abduh's theology; Its impact on his theological system and views. Harun Nasution had called for the revival of the Mu'tazilah theology as an effective means to propel the ummah to greater heights vis-a-vis to the demands of modernization.